Peran Unchr dalam Permasalahan Pengungsi Konflik Ethiophia-Tigray - Feyza Raharsh Lumintosari (Center for Integrative International Studies Laboratory, Faculty of Political and Social Sciences, UIN Sunan Ampel Surabaya, 2021)
The conflict between Ethiopia and Tigray which began in November 2020 is a conflict caused by political and ideological differences between the Federal government of Ethiopia and the Tigray ethnic group until a clash between the two caused thousands of people to die, not only a ceasefire, the Ethiopia-Tigray conflict also caused a humanitarian crisis. one of the reasons is because the Ethiopian federal government has closed access to the Tigray area so that no one can enter or leave the Tigray area and make thousands of other people have to flee to other places due to conditions that are no longer conducive. By using the question how is the role of UNCHR in providing protection for refugees from Tigray, because as an organization that is engaged in refugee issues and is tasked with finding solutions for refugees by collaborating with partners in providing facilities to refugees and providing international protection. This writing uses qualitative methods with library studies which are then analyzed descriptively. Konflik antara Ethiophia dan Tigray yang dimulai pada November 2020 merupakan konflik yang disebabkan oleh Perbedaan politik dan Ideologi antara pemerintahan Federal Ethiophia dan kelompok etnis Tigray hingga terjadi benturan diantara keduannya yang menyebabkan ribuan orang meninggal tidak hanya gencatan senjata konflik Ethiophia-Tigray juga menyebabkan adanya krisis kemanusiaan salah satu penyebabnya adalah karena pemerintah federal Ethiophia menutup akses wilayah Tigray sehingga tidak ada yang bisa masuk atau keluar dari wilayah Tigray dan membuat ribuan orang lainnya harus mengungsi ke tempat lain dikarenakan kondisi yang sudah tidak kondusif lagi. Dengan menggunakan pertanyaan bagaimana peran UNCHR dalam memberikan perlindungan terhadap pengungsi dari Tigray, karena sebagai organisasi yang bergerak dalam permasalahan pengungsian dan bertugas mencari jalan keluar bagi para pengungsi dengan bekerjasama dengan mitranya dalam memberikan fasilitas kepada para pengungsi dan memberikan perlindungan interasional. Penulisan ini menggunakan metode kualitatif dengan studi Pustaka yang kemudian di analisis secara deskriptif.